Effects of Mop Handle Height on Forearm Muscle Activity, Wrist and Upper Arm Posture and Movement During Floor Mopping. Issue 2 (3rd April 2018) - Wallius, Mari-Anne; Bragge, Timo; Karjalainen, Pasi A.; Järvelin-Pasanen, Susanna; Rissanen, Saara M.; Vartiainen, Paavo; Räsänen, Kimmo
OCCUPATIONAL APPLICATIONS: The present study showed that differences in the height of a mop handle affected upper arm postures and movements during floor mopping using a figure-eight method. Higher mop heights increased arm elevation and reduced times at rest. Mop height did not have any significant impact on upper wrist posture, movement or forearm muscle activity. Although the use of a mop at shoulder height increased forearm muscle activity and wrist extension for the lower hand, it did not increase the time spent with substantially-deviated wrist postures. For floor mopping, these results suggest that cleaners should be encouraged to adjust their mop height between shoulder and chin levels in order to utilize the benefits of the telescopic type of mop handle. These results also can be used as a basis for preventive ergonomic training programs and for those involved in developing tools for cleaners.